2005
DOI: 10.1093/njaf/22.4.236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of the Forest Stewardship Program in West Virginia: Ten-Year Assessment

Abstract: Sixty-three percent of the 2,656 West Virginia Forest Stewardship Program (FSP) participants sampled in this study responded to a survey aimed at assessing the implementation rates of the forest management practices recommended in their forest stewardship plans. Logistic regression models were used to determine factors related to the implementation of 10 different forestry practices. Thirty-nine factors were evaluated for these 10 different binary (implemented, not implemented) response variables including lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 0 publications
0
41
1
Order By: Relevance
“…For example, the American Tree Farm System includes 51,000 family forest owners and 33 million acres, but this is only 10% of private forest land in the United States. In West Virginia, USA, Forest Stewardship Program management plans cover over 600,000 acres of private forestland, but this represents only 3,500 of 260,000 private landowners (Jennings and McGill 2005). We have 2 recommendations to rectify this obvious gap between available knowledge and its use by private forest landowners:…”
Section: The Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the American Tree Farm System includes 51,000 family forest owners and 33 million acres, but this is only 10% of private forest land in the United States. In West Virginia, USA, Forest Stewardship Program management plans cover over 600,000 acres of private forestland, but this represents only 3,500 of 260,000 private landowners (Jennings and McGill 2005). We have 2 recommendations to rectify this obvious gap between available knowledge and its use by private forest landowners:…”
Section: The Solutionsmentioning
confidence: 99%
“…1) Public service providers, especially district foresters, Farm Service Agency, and Natural Resources Conservation Service, need a marketing plan. The Forest Stewardship Program participants tend to have large properties, higher incomes, and more education than the average forest landowner (Jennings and McGill 2005). Older rural landowners, with low incomes, little technical education, and no access to the Internet are a difficult audience to reach, yet these owners would benefit most from professional help.…”
Section: The Solutionsmentioning
confidence: 99%
“…Bell et al (1994) showed that attitudes and knowledge of forestry program would be more influential than the monetary incentives suggesting that indirect incentives would be more effective for landowner participation. Jennings and McGill (2005)…”
Section: Programsmentioning
confidence: 99%
“…Even though NIPF landowners have been a topic of extensive studies in other regions, there is very little information about the NIPF owners in the Eastern U.S., and more so in West Virginia. There have been studies on characterizing landowners' participation in Forest Stewardship Program and evaluating the effectiveness of this program in the state (e.g., Egan et al 2001, Magill 2003, Magill et al 2004, Jennings and McGill 2005. A detailed study on the characteristics and the management decisions of NIPF landowners in West Virginia has not been conducted since 1978 (Birch and Kingsley 1978).…”
Section: Introductionmentioning
confidence: 99%
“…The Forest Stewardship Program, promulgated through the 1990 Farm Bill, provides support to private landowners through technical assistance in managing their forestlands through assistance in developing forest management plans for their properties (USDA Forestry Title, n.d. ;Jennings & McGill, 2005). The Farmland Protection Act (2003) led to the creation of West Virginia Farmland Protection Boards which aim to protect agricultural land and woodland as open-space (West Virginia Farmland Protection, 2003, act section, 4) by guiding acquisitions of property, advising and promoting the protection of farmland (Craig, n.d).…”
mentioning
confidence: 99%